Psychoacoustic signal processing techniques in sound reproduction - Toh, Chee Weng. (2008)
Through technology advancement, there is a new trend in the merging of home entertainment system with multimedia applications. An application is watching movies over desktop personal computer with full surround effect comparable to those in the cinemas. However, majority of the standard desktop personal computers are only equipped with a pair of stereo speakers. A new approach is to present phantom audio images, capable of delivering the surround sound effect with only a pair of speakers. By doing so, the number of physical speakers can be reduced drastically for surround sound reproduction.